Adherence to antiretroviral treatment and viral suppression among patients at Unicamp's Hospital de Clínicas: seeking the UNAIDS goal 90-90-90 (Research, Society and Development, 2021)
Objective: to verify adherence to antiretroviral treatment and viral suppression, according to demographic, clinical and laboratory variables in patients seen at the HIV/AIDS outpatient clinic of HC-Unicamp in 2016. Method: cross-sectional study on the demographic, epidemiological and clinical profile of patients treated at the Outpatient Clinic of Infectious Diseases at Hospital Dia of the State University of Campinas Hospital de Clínicas to assess adherence to ART and any adverse events recorded in 2016. Results: of the 339 medical records sampled from PLWHA, 278 (82.0%) with regular use of antiretrovirals and 293 (86.4%) with undetectable viral load (